Complex genomic rearrangements in the dystrophin gene due to replication‐based mechanisms. Issue 6 (15th September 2014) - Baskin, Berivan; Stavropoulos, Dimitri J.; Rebeiro, Paige A.; Orr, Jennifer; Li, Martin; Steele, Leslie; Marshall, Christian R.; Lemire, Edmond G.; Boycott, Kym M.; Gibson, William; Ray, Peter N.
Abstract Genomic rearrangements such as intragenic deletions and duplications are the most prevalent type of mutations in the dystrophin gene resulting in Duchenne and Becker muscular dystrophy (D/BMD). These copy number variations (CNVs) are nonrecurrent and can result from either nonhomologous end joining (NHEJ) or microhomology‐mediated replication‐dependent recombination (MMRDR). We characterized five DMD patients with complex genomic rearrangements using a combination of MLPA/mRNA transcript analysis/custom array comparative hybridization arrays (CGH) and breakpoint sequence analysis to investigate the mechanisms for these rearrangements. Two patients had complex rearrangements that involved microhomologies at breakpoints. One patient had a noncontiguous insertion of 89.7 kb chromosome 4 into intron 43 of DMD involving three breakpoints with 2–5 bp microhomology at the junctions. A second patient had an inversion of exon 44 flanked by intronic deletions with two breakpoint junctions each showing 2 bp microhomology. The third patient was a female with an inherited deletion of exon 47 in DMD on the maternal allele and a de novo noncontiguous duplication of exons 45–49 in DMD and MID1 on the paternal allele. The other two patients harbored complex noncontiguous duplications within the dystrophin gene. We propose a replication‐based mechanisms for all five complex DMD rearrangements. This study identifies additional underlying mechanisms in DMD, and provides insight into the molecular bases of these genomic rearrangements.